2019
DOI: 10.1152/ajpendo.00156.2018
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle interstitial fluid metabolomics at rest and associated with an exercise bout: application in rats and humans

Abstract: Zhang J, Bhattacharyya S, Hickner RC, Light AR, Lambert CJ, Gale BK, Fiehn O, Adams SH. Skeletal muscle interstitial fluid metabolomics at rest and associated with an exercise bout: application in rats and humans. Blood or biopsies are often used to characterize metabolites that are modulated by exercising muscle. However, blood has inputs derived from multiple tissues, biopsies cannot discriminate between secreted and intracellular metabolites, and their invasive nature is challenging for frequent collections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…Proteomics studies have identified proteins that are unique to ISF, unique to plasma, or found in both compartments (5)(6)(7). Similarly, the transcriptome and the metabolome of ISF show resemblance to plasma but with distinct differences (8)(9)(10). These studies suggest that ISF could be used as a surrogate for plasma for the study of certain biomolecules, but also that nonoverlapping information can be gained by analyzing ISF.…”
Section: Introductionmentioning
confidence: 96%
“…Proteomics studies have identified proteins that are unique to ISF, unique to plasma, or found in both compartments (5)(6)(7). Similarly, the transcriptome and the metabolome of ISF show resemblance to plasma but with distinct differences (8)(9)(10). These studies suggest that ISF could be used as a surrogate for plasma for the study of certain biomolecules, but also that nonoverlapping information can be gained by analyzing ISF.…”
Section: Introductionmentioning
confidence: 96%
“…Although food was only allowed after the 3-h post-exercise biopsy, the sample collection delay represents a limitation to this study that may have hindered observation of additional exercise-induced metabolite changes in both trained and untrained horses. Moreover, a noteworthy point raised by Zhang and colleagues [ 101 ] is that muscle biopsies do not allow distinction between extra- and intra-muscular metabolites. To do so, investigating skeletal muscle interstitial fluids is a promising, yet rarely practiced avenue in metabolomics research that has the potential to provide more accurate insights into mammalian muscle metabolism.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regumentioning
confidence: 99%
“…Out of 299 detected metabolites, only 43% were common to both biofluids. Among the 204 metabolites changed by exercise, only 20% were shared, therefore underscoring the limited ability of circulating metabolites to reflect the full range of muscle metabolic changes induced by exercise [ 101 ]. Additional pilot data from human muscle interstitial fluid was also collected in this study and, in line with rat data, reported increased TCA cycle intermediates following exercise, possibly induced by increased FA oxidation.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regumentioning
confidence: 99%
“…A few human [ 56 58 ], equine [ 23 , 59 62 ] and rodent [ 20 , 63 , 64 ] studies have looked into shifts in blood metabolomic profiles in response to training. However, the circulation as body compartment connects to all organ systems, such as the liver, gastro intestinal tract, etc., which makes it nearly impossible to link these study results one on one to shifts in muscle metabolism, as has been shown by Zhang et al [ 17 ].…”
Section: Introductionmentioning
confidence: 97%
“…Ideally, these adaptations are ultimately seen in the main muscle groups responsible for force and locomotion necessary for a certain sports discipline. Since each of these muscle fiber types uses its own specific set of main metabolic pathways, shifts also take place in the metabolic fingerprint of muscle groups in response to training [16][17][18][19][20][21][22][23]. On top of that, not all muscles show the same adaptation in response to a certain type of training.…”
Section: Introductionmentioning
confidence: 99%